Advances in Sustainable Chemical Process: Catalysis, Renewable, and Water Reduction - Yasin, Muhammad; Khalid, Sadaf; Yasir, Muhammad; Ayub, Sibgha (Indus Journal of Bioscience Research, 2025)
This review paper critically analyzes the latest advancements in sustainable chemical processes and concentrates on three key areas, which are catalysis, integration of renewable energy sources, and technologies to reduce water consumption. Catalysis is very crucial in attaining an efficient transformation in chemical reactions as new and exciting developments related to non-precious metal catalysts and biocatalysis are improving more sustainable, lower-cost pathways while minimizing damaging byproducts. There is a significant need for renewable energy sources, particularly in solar, wind, and biomass, in the production of chemicals to reduce dependence on fossil fuels, decrease carbon emissions, and pave the way for a sustainable energy future. On the other hand, water-saving technologies, particularly closed-loop water systems and waterless chemical processes, are likewise crucial to mitigate increasing shortages in access to clean water, reducing the water footprint associated with industrial operations. Finally, the paper reviews barriers and opportunities to scale up these technologies into economically viable, technically feasible operations requiring appropriate policy support. It seeks to point out continued research and technological development and interindustry cooperation in an effort to move beyond these hurdles toward a more sustainable and resource-efficient chemical industry. Through the integration of catalysis, renewable energy, and water reduction strategies, the chemical industry has the potential to substantially diminish its environmental impact and advance global sustainability objectives.